Mixing of inclined dense jets in shallow coastal waters - Jiang, Baoxin (2015)
Nowadays, the rapid growth of world population, urbanization and industrialization are all contributing to the increasing demand for fresh water. With the security of feed water from the sea and the advancement in membrane technology, seawater desalination, especially seawater reverse osmosis, is gaining popularity as a viable alternative to augment the water supply for expanding coastal cities around the world. From an environmental point of view, the brine outfall of desalination plants needs to be designed effectively such that the dense effluent can mix well with the surrounding ambient coastal waters. Many previous studies had previously investigated the subject of inclined dense jets for the brine discharge, in which cases a full submergence of the dense jet was generally targeted as the typical design scenario. However, the wider range of discharge flowrate nowadays is challenging the design of the brine outfall, with good mixing needs to be ensured for the entire range. Together with a general desire for cost minimization such that the outfall should be located as close to the shore as environmentally acceptable, the current design practice of providing complete submergence to the dense jet may thus need to be reassessed. In other words, we need to examine the possibility of the inclined dense jet coming into contact with the water surface in shallow coastal waters, and investigate the resulting influence on the mixing characteristics. The present study investigated the effects of the shallow ambient water depth on the mixing behavior of inclined dense jets, derived the semi-analytical solutions for the design of non-interfering multiport brine diffusers, and finally proposed the concept of the swirling brine outfall with the detailed investigation of the swirl effect on the dense jet mixing.